A Network for Advancing Dendrochronology, Dendrochemistry and Dendrohydrology in South America - Aguilera-Betti I. (2020)
Tree-ring research (TRR) in South America (SA) continues to make important contributions in multiple sub-disciplines, including dendrochemistry and dendrohydrology. This report describes some of the advances in TRR in SA presented in a two-day International Meeting Research entitled "An International Network to Promote Advances in Dendrochronology in South America", organized by the Laboratory of Dendrochronology and Environmental Studies of the Pontifical Catholic University of Valparaíso in Valparaíso, Chile, on January 21-22, 2019. The objective of the meeting was to communicate recent advances in TRR within a network of laboratories in Argentina, Brazil, Chile, Peru, and Uruguay. Novel methodologies and results in dendrochemistry and wood anatomy were also presented by collaborating researchers from German institutions. This report describes some of the research within the subdisciplines of tree-ring science, including dendrochemistry, anatomy and dendrohydrology, and their application to understanding spatio-temporal variability in heavy metal contamination, climate, hydrology, fire regimes and other critical components of South American forest and woodland ecosystems. The meeting demonstrated expansion and diversification of inquiry and applications of TRR in SA, whereby collaboration across research centers has been critical for the advances made in broad-scale comparative studies as well as multi-proxy approaches and the study of global and hemisphere-scale climate phenomena. Copyright © 2020 by the Tree-Ring Society.